2021
DOI: 10.33861/2071-8020-2021-5-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Features of cobuvirus infection of farm animals

Abstract: Data on the cobuvirus causing outbreaks of diseases in humans and animals, on the clinical signs of the disease and the distribution area are presented in the article. Literature data indicate that since the end of the 20th and the beginning of the 21st centuries, cases of cobuvirus infection have been registered, manifested by massive gastrointestinal diseases in humans, as well as young animals: large horned cattle, sheep, goats, roe deer, pigs (domestic and wild), rabbits, dogs, foxes, bats, ferrets and bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies using a local strain called Ismailia, a live attenuated LSDV vaccine, have reported that all calves in the study were registered to have protective antibodies by both ELISA and serum neutralization test (SNT) at 30 weeks and were still registering protective antibodies at 40 weeks when investigated via the ELISA [38]. For the specific prevention of LSDV, a homologous live attenuated virus (LAV) vaccine from the Neethling virus strain is commonly used, and it induces long-lived immunity for 3 years [39]. Additionally, a heterologous LAV vaccine utilizing sheep pox virus has been shown to induce strong cross-immunity for 2 years [40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using a local strain called Ismailia, a live attenuated LSDV vaccine, have reported that all calves in the study were registered to have protective antibodies by both ELISA and serum neutralization test (SNT) at 30 weeks and were still registering protective antibodies at 40 weeks when investigated via the ELISA [38]. For the specific prevention of LSDV, a homologous live attenuated virus (LAV) vaccine from the Neethling virus strain is commonly used, and it induces long-lived immunity for 3 years [39]. Additionally, a heterologous LAV vaccine utilizing sheep pox virus has been shown to induce strong cross-immunity for 2 years [40].…”
Section: Discussionmentioning
confidence: 99%